"The solitude absorbs and it oppresses": 'Illegality' and its implications on Latino immigrant day laborers' social isolation, loneliness and health. (March 2021) - Negi, Nalini Junko; Siegel, Jennifer L.; Sharma, Priya B.; Fiallos, Gabriel
Abstract: Despite a well-documented relationship between social isolation and health among men, this link has been understudied among marginalized populations such as undocumented immigrant men whose structural social exclusion may impede the cultivation and maintenance of social connections in the United States. This may be particularly so in new immigrant settlement cities that may lack an established Latina/o community or the social infrastructure often needed to ease the process of social integration. Studies that have examined social disconnectedness, social isolation, and/or loneliness have largely focused on individual level factors (i.e., older age) that may precipitate or contextualize experiences of social isolation, social support and social networks. Missing from such conceptualizations is a consideration of the role of structural factors, such as "illegality" among undocumented immigrant men, on experiences of social disconnection, social exclusion, social isolation and loneliness and resultant adverse health behaviors. This study, through in-depth qualitative participant narratives, explores the social condition of one group of "illegal" immigrant men, Latino immigrant day laborers (LIDL), and their experiences of social exclusion, social isolation, loneliness and health in the new immigrant settlement city of Baltimore. Using an ethnographic methodological approach, eight focus groups (N = 37) were conducted with participants recruited from two day labor sites from 2016 to 2019. Thematic analysis revealed a structural process of social exclusion and disconnection that exposed LIDLs to experiences of racism, structural vulnerability, and dehumanization which in turn may have heightened social isolation and loneliness and patterned substance use and sexual risk taking. Findings further emphasize the potential conceptual significance of structurally induced social disconnection, as distinct from lack of social support, in the study of LIDLs' social isolation, loneliness and health. Highlights: Social exclusion and "illegality" pattern social relationships and health. Day laborers' experience social exclusion, disconnection, racism and dehumanization. Social isolation and loneliness may lead to adverse health behavior in this group.